EFEKTIVITAS BUKU “KAIFA TUSHOLLY” DALAM MENINGKATKAN PEMAHAMAN TATA CARA SHOLAT DI SDI SAHABAT BERLIAN - Saifudin, Drs (Rihlah Review: Jurnal Pendidikan Islam, 2024)
The book “Kaifa Tushally” is utilized at SDI Sahabat Berlian to enhance the understanding of prayer procedures. Through a clear and structured approach, the book provides easily understandable explanations of each step of prayer, from intention to salutation. Supported by engaging illustrations and concise yet comprehensive explanations, the material facilitates students’ comprehension of these concepts. Additionally, the book offers practical exercises enabling students to directly apply their knowledge. The research method employed was a One-group pre-test-post-test design. The research sample consisted of students before and after using the “Kaifa Tushally” book. Measurements were taken before and after the intervention using a pre-designed test of prayer procedure understanding. The results of the study indicate a significant improvement in the understanding of prayer procedures among students after using the “Kaifa Tushally” book. The group utilizing the book showed a higher average test score after the intervention. This suggests that the “Kaifa Tushally” book is effective in enhancing the understanding of prayer procedures at Sahabat Berlian Islamic Elementary School. From these research findings, it can be concluded that the “Kaifa Tushally” book is an effective resource in the context of learning prayer procedures at the elementary school level. The emphasis on clear explanations, engaging illustrations, and practical exercises aids students in better grasping these concepts. Therefore, recommendations for further use of the “Kaifa Tushally” book in the context of Islamic education at the elementary school level can be drawn from this research.